Unwanted effects of treatments for depression in children and adolescents: a mapping of systematic reviews - Astrid Dahlgren; Lise Mette Eidet; Mari Elvsåshagen (BMJ Open)
Objectives To describe the results of a mapping review exploring the coverage of unwanted treatment effects in systematic reviews of the effects of various treatments for moderate to severe depression in children and adolescents.Setting Any context or service providing treatment for depression, including interventions delivered in local communities and school settings, as well as services provided in primary or specialist care.Participants Children and young people with moderate to severe depression (<18 years).Interventions Systematic reviews published in 2011 or later comparing the effects of any treatment for children and adolescents with moderate to severe depression meeting the Database of Abstracts of Reviews of Effects criteria. The systematic search was performed in April 2018 and updated in December 2018.Primary outcomes Any unwanted effects of treatments as defined in the systematic review.Results We included 10 systematic reviews covering 19 treatment comparisons. Unwanted effects were assessed for seven of 19. Three comparisons were evaluations of pharmaceutical interventions or combination therapy, reporting effects on ‘suicidal ideation’ and ‘suicide risk’. Two included therapy, reporting ‘self-harm’, and ‘suicidal ideation’, and two comparisons included transcranial magnetic stimulation and electroconvulsive treatment. Unwanted effects evaluated for these treatments were mostly symptoms of physical discomfort such as headache or cramps. For the remaining treatment comparisons evaluating psychological and psychosocial therapies, unwanted effects were not evaluated or found. A limitation of overviews of systematic reviews such as this mapping study is that data extraction is done based on the reporting of results by the review authors and not on the primary studies.Conclusion The unwanted effects of widely used treatments for children and young people with depression is unknown. This is a major barrier for evidence informed decision making about treatment choices for children and young people. We suggest that unwanted effects should be a reporting standard in all protocols describing evaluations of treatments, including primary studies as well as systematic reviews.